Family joint activities in a cross-national perspective - Kuntsche Emmanuel; Borup Ina; Zemaitiene Nida; Zaborskis Apolinaras; Moreno Carmen (BMC, 2007)
Abstract Background Parents and children joint activities are considered to be an important factor on healthy lifestyle development throughout adolescence. This study is a part of the Cross-National Survey on Health Behaviour in School-aged Children - World Health Organization Collaborative Study (HBSC). It aims to describe family time in joint activities and to clarify the role of social and structural family profile in a cross-national perspective. Methods The research was carried out according to the methodology of the HBSC study using the anonymous standardized questionnaire. In total, 17,761 students (8,649 boys and 9,112 girls) aged 13 and 15 years from 6 European countries (Czech Republic, Finland, Greenland, Lithuania, Spain, and Ukraine) were surveyed in the 2001-2002 school-year. The evaluation of joint family activity is based on 8 items: (1) watching TV or a video, (2) playing indoor games, (3) eating meals, (4) going for a walk, (5) going places, (6) visiting friends or relatives, (7) playing sports, (8) sitting and talking about things (chatting). Results Students from Spain and Ukraine reported spending the most time together with their families in almost all kinds of joint activities, whereas students from Greenland and Finland reported spending the least of this time. Boys were more likely than girls to be spending time together with family. Joint family activity goes into decline in age from 13 to 15 years. Variability of family time in a cross-national perspective was relatively small and related to children age category. Considering national, gender and age differences of studied population groups, we found that the distribution of joint family activities tends to be dispersed significantly by family structure (intact/restructured family) and family wealth. Conclusion Our study compares children and parent joint activities in European countries and reveals differences and similarities in these patterns between countries. The findings underline the role of family structure (intact/restructured family) and family wealth in the distribution of time spent in joint family activities, which should be considered by health promoters.